PROPOSING AMENDMENTS TO THE SINGAPORE S BUILDING AND CONSTRUCTION INDUSTRY SECURITY OF PAYMENT ACT IN THE ASPECT OF ADJUDICATION OF THE FINAL PAYMENT CLAIM: A DELICATE BALANCING ACT - NGUYEN CHI DAT (2017)
Bachelor's